1994
DOI: 10.1002/app.1994.070541115
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of glycolysis of poly(ethylene terephthalate) melts

Abstract: SYNOPSISThe reaction of poly(ethy1ene terephthalate) (PET) melts with ethylene glycol was examined in a pressure reactor at temperatures above 245°C. The reaction rate was found to depend on temperature and on the concentrations of liquid ethylene glycol and of ethylene diester groups in the polymer. A kinetic model proposed for the initial period of the reaction was found to be consistent with experimental data. It was found that internal catalysis by ethylene glycol does not play a n important role in the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
3
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 10 publications
4
80
3
3
Order By: Relevance
“…Studies on the kinetics of PET glycolysis (Campanelli et al, 1994b;J. Chen & L. Chen, 1999) have shown that glycolysis without a catalyst is very slow and complete depolymerization of PET to BHET cannot be achieved.…”
Section: Glycolytic Depolymerization Of Petmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the kinetics of PET glycolysis (Campanelli et al, 1994b;J. Chen & L. Chen, 1999) have shown that glycolysis without a catalyst is very slow and complete depolymerization of PET to BHET cannot be achieved.…”
Section: Glycolytic Depolymerization Of Petmentioning
confidence: 99%
“…Although metal salts are effective in increasing the PET glycolysis rate, it should be noted that zinc salts, and presumably other metal salts, have a catalytic effect on glycolysis of PET only below 245 °C, and apparently do not promote any further increase in the reaction rate above that temperature due to mass transfer limitations (Campanelli et al, 1994b). Thus, a need to develop new catalysts that can overcome this limitation.…”
Section: Metal Saltsmentioning
confidence: 99%
“…• b -uso de altas temperaturas [8][9][10] ; e • c -altas pressões [10,11] . Em trabalhos recentes Ruvolo Filho e colaboradores estudaram a despolimerização do PET [12][13][14][15] e mostraram usando soluções de NaOH em etilenoglicol 1,1 mol.L -1 [12] que a cinética de despolimerização abaixo da temperatura de fusão do PET é um processo heterogêneo que ocorre na superfície do PET e depende da velocidade de agitação em que é realizada a reação.…”
Section: Methodsunclassified
“…Outros pesquisadores tem estudado a reciclagem do PET [16][17][18][19][20][21][22][23][24] e encontrado resultados semelhantes usando solução aquosa de NaOH em proporções equimolares com PET em temperaturas e ou pressões menores mas, em maiores tempos de reação [16][17][18][19][20] . Existem poucos trabalhos usando catalisadores [9] para aumentar o rendimento da reação de despolimerização do PET.…”
Section: Methodsunclassified
“…The activation energy for the uncatalyzed glycolysis is about 32 kcal/mol, whereas a proper catalyzed process requires less than 20 kcal/mol [25]. Thus, various metal-containing catalysts, such as zinc acetate [26][27][28][29][30], lead-, cobalt-or manganese acetate [26,29,30] and titanium alkoxides [31] or other titanium compounds [5,25] such as titanium (IV)-phosphate compound were used to facilitate the process. Zinc acetate is the most efficient catalyst in comparison with other metal-acetate compounds.…”
Section: Introductionmentioning
confidence: 99%